Contusion Index is an Important Tool for the Management of Traumatic Intracerebral Hematoma - Khaliq, Adnan; Ali, Mumtaz; Azam, Farooq; Gul, Nayab; Chaurasia, Bipin (Indian Journal of Neurotrauma, 2021)
Objective This article evaluates outcome of traumatic intracerebral hematomas in terms of Glasgow Coma Scale (GCS) after medical or surgical management according to contusion index.Materials and Methods This descriptive study was conducted in the Department of Neurosurgery, Lady Reading Hospital, Peshawar, Pakistan from January 2017 to December 2018. Total number of patients with traumatic intracerebral contusions included in this study was 60 with age between 5 and 75 years. Both male and female were included. Patients with other coexisting traumatic intracranial hematomas like extradural hematoma, subdural hematoma, and polytrauma were excluded from this study. Contusion index of patients were calculated by noncontrast-enhanced computed tomography brain. On arrival patient GCS was documented. The management protocol, that is, conservative or surgical, was provided to individual patient according to contusion index as calculated. Outcome of management was assessed in terms of GCS.Results Patients with contusion index of 0 to 4 were managed conservatively. Patients with contusion index of 6 were offered surgical management. Patients with contusion index of 9 had poor outcome with both conservative and surgical management.Conclusion Contusion index can be used reliably as a tool for management of isolated traumatic intracerebral hematomas
Keywords: contusion index; Glasgow Coma Scale; head injury; intracerebral contusions